(untitled) (International relations and international law Journal, 2023)
This article analyzes the role of the media, in particular the Internet, in the voting practices of youth in the Central Asian region. The study raises the question: How does access and frequency of Internet use relate to participation in the political process? The political process refers to interest in politics, interest in the institution of elections, and involvement in the voting process. The focus is on young people aged 14-30 from Central Asian countries: Kazakhstan, Kyrgyzstan, Uzbekistan and Tajikistan. The purpose of the study is to conduct a comparative analysis of the political practices of young people from four Central Asian countries and determine the influence of traditional media and the Internet in the formation of the political and social capital of young people. As an empirical basis, the article uses survey data conducted by the Friedrich Ebert Foundation. Based on these data, the work conducts a comparative descriptive and correlational analysis of four Central Asian countries. The results obtained indicate that the Internet is a significant factor in the formation of interest in politics. At the same time, however, traditional media such as television continue to play a more significant role in this process. Work on the influence of the media on the formation of political behavior and political learning among young people remains understudied in the context of Central Asia, so this work fills an important gap in the literature. In general, studies of the interaction between the media and the political system are important for a more complete understanding of the political situation and development in the Central Asian region.